America & Islam soundbites, suicide bombs and the road to Donald Trump - Pintak, Lawrence 1955- (London New York Oxford New Delhi Sydney I.B. Tauris, 2019)
"Donald Trump's first term as the 45th President of the United States of America has shocked the world. His attitudes towards Islam became a key point of contention on the campaign trail, and in power Trump has continued his war of divisive words and deeds. Here, acclaimed journalist Lawrence Pintak scrutinizes America's relationship with Islam since its foundation. Casting Donald Trump as a symptom of decades of misunderstanding and demonization of the Islamic world, as well as a cause of future tensions, Pintak shows how and why America's relationship with the world's largest religion has been so fractious, damaging and self-defeating. Featuring unique interviews with victims and perpetrators of Trump's policies, as well as analysis of the media's role in inflaming debate, America & Islam seeks to provide a complete guide to the twin challenges of terrorism and the polarizing rhetoric that fuels it, and sketches out a future based on co-operation and the reassertion of democratic values--"Bloomsbury Publishing
Table of Contents -- Reviews ix -- About the Author xi -- Author's Note xiii -- Introduction 1 -- Section I: Politics - The -- Muslim Bogeyman 9 -- Chapter 1: Media -- Codependence 11 -- Chapter 2: Prisoners of -- The Long War 31 -- Chapter 3: The American -- Taliban 47 -- Chapter 4: Cogitative -- Dissonance 53 -- Chapter 5: The Morning -- After 59 -- Section II: (Mis)Perceptions -- - Separating Fact from Fiction 71 -- Chapter 6: Not All -- Islamists Want Your Head 73 -- Chapter 7: The Myth of -- the Muslim Monolith 81 -- Chapter 8: How the West -- Created Radical Islam 101 -- Chapter 9: The Islamic -- States of America 123 -- Section III: Policies - -- Seeing Black & White in a Sea of Gray 141 -- Chapter 10: Brotherhood -- of the Orb 143 -- Chapter 11: The Wahhabi -- Project 153 -- Chapter 12: Tempest in -- the Gulf 165 -- Chapter 13: Between Iran -- and a Hard Place 173 -- Chapter 14: Return of the -- Ottomans 183 -- Section IV: Prospects - -- Islam Beyond Trump 189 -- Chapter 15: The Prince 191 -- Chapter 16: The -- Americanization of Islam 199 -- Chapter 17: Voices of -- Reason 211 -- Chapter 18: Islam -- UnTrumped 219 -- Postscript 231 -- Notes 235 -- Bibliography 277 -- Index.
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Trump, Donald -- 1946- -- Political and social views; Islam and politics -- United States; United States -- Politics and government -- 2017-; United States -- Foreign relations -- 2017-; Electronic books